Effect of expertise and visual contribution on postural control in soccer - Paillard, T.; Noe, F. (Scandinavian Journal of Medicine & Science in Sports, 2006)
This work analyzes the postural performance and the use of visual information in soccer players according to their level of competition. Two groups of healthy soccer players were investigated at the mid-competition season: an amateur (AM) (n=15) group composed of regional-level players and a professional group at a national level (PRO) (n=15). Posture was assessed by measuring the center of foot pressure (COP) with a force platform during a test (51.2 s) of bipedal quiet standing posture. The test was completed with eyes open (the subjects looked at a fixed-level target at a distance of 2 m) and closed (they kept their gaze in a straight-ahead direction). The statistical analysis showed that PRO soccer players were more stable than AM soccer players. Moreover, the contribution of vision in postural maintenance was less important in the PRO players than in the AM players. The present study suggests that intense training allows PRO soccer players to become less dependent on vision to control their posture such that vision can be dedicated to treating the information, that emanates from the game.